Queen of all mayhem : the blood-soaked life and mysterious death of Belle Starr, the most dangerous woman in the West - Huckelbridge, Dane (William Morrow, an imprint of HarperCollins Publishers, 2025)
"A riveting, deeply researched, blood-on-the-spurs biography of Belle Starr, the most legendary female outlaw of the American West"-- Provided by publisher.